1993
DOI: 10.1016/0960-1686(93)90210-p
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the nocturnal boundary layer on secondary trace species in the atmosphere at Dorset, Ontario

Abstract: Abstract-The impact ofthe nocturnal boundary layer (NBL) on the concentrations of03' H 2 0 2 , PAN and CH20 has been studied for two 4-day periods, one in the summer of 1989 and the other in the spring of 1990. Where the presence of the nocturnal layer is clear, 03' PAN and CH 2 0 concentrations decrease rapidly and these species appear to be deposited to the surface. Break-up of the inversion in the morning returns concentrations to levels typical ofthe previous day. H 2 0 2 is removed much faster than the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Stable nocturnal boundary layer heights typically range from ∼50-200 m at midlatitude continental locations (e.g., Hastie et al, 1993;Gusten et al, 1998;McKendry and Lundgren, 2000;White et al, 2003); thus we chose 125 m as a representative value for the TF site (e.g., Talbot et al, 2005;Sive et al, 2007;Mao et al, 2008;White et al, 2008;. If we use H =50 m or 200 m, our emission rate estimates discussed below vary by ±60%.…”
Section: Emission Rates Estimated From Observations At Tfmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable nocturnal boundary layer heights typically range from ∼50-200 m at midlatitude continental locations (e.g., Hastie et al, 1993;Gusten et al, 1998;McKendry and Lundgren, 2000;White et al, 2003); thus we chose 125 m as a representative value for the TF site (e.g., Talbot et al, 2005;Sive et al, 2007;Mao et al, 2008;White et al, 2008;. If we use H =50 m or 200 m, our emission rate estimates discussed below vary by ±60%.…”
Section: Emission Rates Estimated From Observations At Tfmentioning
confidence: 99%
“…We followed a simple box model approach which has been effectively used in previous studies to calculate emission and removal rates of trace gases in this region (i.e., Talbot et al, 2005;Zhou et al, 2005;Sive et al, 2007;White et al, 2008;Russo et al, 2010). This method uses measurements made on nights with low wind speeds and when a stable inversion layer has developed because under these conditions, the exchange of air between the nocturnal boundary layer (NBL) and the residual layer above is limited (e.g., Hastie et al, 1993;Gusten et al, 1998;Talbot et al, 2005). Therefore, advection and vertical mixing of air masses can be neglected.…”
Section: Emission Rates Estimated From Observations At Tfmentioning
confidence: 99%
“…It is generally felt that daytime measurements, after the breakup of the NBL, are truly representative because of the high turbulence, especially in the summer. The interpretation of nighttime data is more difficult because of the stratification of the atmosphere (Hastie et al, 1993;Shepson et al, 1992). The flights of 1 August allow us to examine this problem for both N0 2 and 0 3 , For these compounds, N0 2 has a surface source whereas 0 3 has a surface sink.…”
Section: How Representative Are Ground-based Measurements?mentioning
confidence: 99%
“…3. All of them have clear spectral peaks at semi-diurnal and diurnal frequencies, corresponding to the local rush-hour emissions in the mornings and evenings and the photochemical reactions variability, respectively, in addition to the diurnal planetary boundary layer evolutions driven primarily by the daytime heating and nighttime cooling at the surface (e.g., Hastie et al, 1993;Güsten et al, 1998;Talbot, 2004, Talbot et al, 2005;Stephens et al, 2008). Among NO, NO 2 , NO x , CO, and SO 2 spectra, these two peaks have about the same pattern, i.e., the diurnal one is stronger than the semi-diurnal one.…”
Section: Power Spectramentioning
confidence: 99%
“…However, there is still a lack of information on how chemical species are related to various dynamical scales in both time and space. Of course, the basic diurnal and semidiurnal oscillations found in the chemical observations (e.g., Hastie et al, 1993;Güsten et al, 1998;Talbot, 2004, Talbot et al, 2005;Stephens et al, 2008) are caused by variations in photochemical reactivity and traffic emissions, respectively, in addition to the diurnal boundary-layer variability. Stephens et al (2008) identified weekly signals in their study of the atmospheric chemical constituents in Mexico City, most likely due to the lower weekend emissions of ozone (O 3 ) precursors including nitrogen oxides (NO x , i.e., NO and NO 2 ) and reactive volatile organic compounds (VOCs), and reported references on this subject for other major cities and metropolitan regions.…”
Section: Introductionmentioning
confidence: 99%